2014
DOI: 10.7146/ocps.v15i1.15827
|View full text |Cite
|
Sign up to set email alerts
|

Is Evidence-based medicine about democratizing medical practice?

Abstract: The authoritarian standpoint in medicine has been under challenge by various groups and researchers since the 1980s. The challenges have been ethical, political and medical, with patient movements at the forefront. Over the past decade, however, a deep challenge has been posed by evidence-based medicine (EBM), which has challenged the entire strategy of medical treatment from the point of view of a self-critical, anti-authoritarian and hereby also (it has been claimed) a more democratic medical practice. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…We found that, in order for conversation to nurture trust, there is need for the student to lead the way, but not with the kind of paternalistic authority that medical doctors traditionally have adhered to. 13,38 For decades, faculty, researchers and doctors have taken such authority for granted. This is based on the assumption that “doctors have intrinsically superior insights and that patients should defer to their edicts.” 13 The patients of our study crave an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…We found that, in order for conversation to nurture trust, there is need for the student to lead the way, but not with the kind of paternalistic authority that medical doctors traditionally have adhered to. 13,38 For decades, faculty, researchers and doctors have taken such authority for granted. This is based on the assumption that “doctors have intrinsically superior insights and that patients should defer to their edicts.” 13 The patients of our study crave an alternative.…”
Section: Discussionmentioning
confidence: 99%